Evaluation of antibiotic resistance genes expression in food poisoning Salmonella typhimurium isolated from retail pork in Ha Noi - Thu, Nguyen Thi Hoai; Viet, Nguyen Thanh; Quyen, Nguyen Thi Nha; Minh, Nghiem Ngoc; Bich Thuy, Vo Thi (Academia Journal of Biology, 2017)
Salmonella is the most common bacteria causing foodborne diseases. Millions of cases of infections and hundreds of thousands of deaths every year worldwide. Salmonella consists of more than 2,500 serovars. Among those, Salmonella typhimurium (ST) is one of the major causes of food poisoning in humans with the most powerful antibiotic resistance, causing damage to the livestock and affecting public health. Foods of animal origin, especially pork have long been recognized as the primary source of  Salmonella to cause human infections. In this study, three strains of ST causing food poisoning were isolated from retail pork in Hanoi. They were resistant to ampicillin, streptomycin, tetracycline (100%), chloramphenicol, sulfamethoxazole/trimethoprim (66.7%), and gentamycin (33.3%). Seven genes (e.g. aadA, avrA, gyrB, prmA, sul II, tetA and blaTEM/TEM) encoding seven different antibiotic resistance groups were detected from three strains of ST with the highest percentage (100%). The relative seven genes per control gene (16S rRNA) expression were above 65%. The presence of antibiotic resistance genotypes among ST isolated from retail pork in Hanoi is worrisome, especially, when people use food contaminated with these STs, the genomes of the bacteria may transmit in the human genome and lead to antibiotic resistance in humans. Citation: Nguyen Thi Hoai Thu, Nguyen Thanh Viet, Nguyen Thi Nha Quyen, Nghiem Ngoc Minh, Vo Thi Bich Thuy, 2017. Evaluation of antibiotic resistance genes expression in food poisoning Salmonella Typhimurium isolated from retail pork in Ha Noi. Tap chi Sinh hoc, 39(2): 212-222. DOI: 10.15625/0866-7160/v39n2.9370. *Corresponding author: thuytbvo@igr.ac.vn Received 11 December 2016, accepted 20 March 2017